Bernardo Vega. Trujillo y las Fuerzas Armadas Norteamericanas. Santo Domingo, Fundación Cultural Dominicana, 1992. 520 p - Cassá, Roberto (Universidad Autónoma de Santo Domingo (UASD), 1993)
No precisa de un resumen.